2015 IEEE 27th International Conference on Tools With Artificial Intelligence (ICTAI) 2015
DOI: 10.1109/ictai.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

MILP for the Multi-objective VM Reassignment Problem

Abstract: Machine Reassignment is a challenging problem for constraint programming (CP) and mixed integer linear programming (MILP) approaches, especially given the size of data centres. The multi-objective version of the Machine Reassignment Problem is even more challenging and it seems unlikely for CP or MILP to obtain good results in this context. As a result, the first approaches to address this problem have been based on other optimisation methods, including metaheuristics. In this paper we study under which condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The authors proposed a three-step method to address the problem, using a modified version of the ROADEF challenge [43]. In [44] and [41] the authors proposed a linear formulation of the problem and studied the relevance of using MILP and Constraint-Based LNS (CBLNS) solvers. They showed that MILP solvers (e.g., IBM ILOG CPLEX) can only solve small instances, whereas CBLNS achieves worse results than MILP solvers on small instances, but scales well to larger ones.…”
Section: Multi-objective Vm Reassignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed a three-step method to address the problem, using a modified version of the ROADEF challenge [43]. In [44] and [41] the authors proposed a linear formulation of the problem and studied the relevance of using MILP and Constraint-Based LNS (CBLNS) solvers. They showed that MILP solvers (e.g., IBM ILOG CPLEX) can only solve small instances, whereas CBLNS achieves worse results than MILP solvers on small instances, but scales well to larger ones.…”
Section: Multi-objective Vm Reassignmentmentioning
confidence: 99%
“…However, most solutions to this problem in the literature use a weak definition of multiobjective [35], i.e., a linear aggregation of objectives [1,29,23]. Related work also often miss the complexity of large companies, where the infrastructure is not monolithic but distributed over decentralised hosting departments with their own preferences [43,44]. The optimisation of the companies' IT infrastructure is then more challenging as decisions have to take into account the preferences of the capital allocators of each hosting departments and the interests of the company as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…The initial population is generated by the first step of our hybrid algorithm, which gives a good bootstrap to the evolutionary algorithm. Note that we use all individuals from the first step as seeds [24], unlike in [26], [27] where only few good individuals are added to the initial population.…”
Section: B Secondmentioning
confidence: 99%
“…Fuzzy pattern recognition [44], heuristic algorithms [45], [46] and evolutionary algorithms [47] are commonly used in multiobjective optimization for high-level (i.e., coarse-grained) resource allocation, which attempt to find an appropriate solution between system performance (e.g., response time) and useroriented constraints (e.g., SLAs). Similarly, liner programming or dynamic programming can be used to solve VM placement problems [48]- [50] for low-level (fine-grained) resource placement, focusing on optimizing resource utilization and power consumption [51].…”
Section: ) Cell Managermentioning
confidence: 99%